Antimicrobial activity of Plumbago indica and ligand screening of plumbagin against methicillin-resistant Staphylococcus aureus. Issue 7 (3rd May 2022) - Dissanayake, D. M. I. H.; Perera, D. D. B. D.; Keerthirathna, L. R.; Heendeniya, Saumya; Anderson, Raymond J.; Williams, David E.; Peiris, L. Dinithi C.
Abstract: In this study, the antimicrobial properties of Plumbago indica root bark against bacterial strains and a fungal strain were investigatedusing the disc diffusion and minimum inhibitory concentration assays. Gas chromatography/mass spectrometry, nuclear magnetic resonance spectrometry, and column chromatography analyses were conducted to identify and isolate the active compounds. A docking study was performed to identify possible interactions between the active compound and DNA gyrase using the Schrödinger Glide docking program. Both methanol extract and the ethyl acetate fraction of the root bark showed significant antimicrobial activity against the gram-positive bacteria than against the gram-negative bacteria and the fungal strain. The active compound was identified as plumbagin. A disc diffusion assay of plumbagin revealed potent antimicrobial activity against methicillin-resistant Staphylococcus aureus. Molecular docking of plumbagin revealed high specificity towards the DNA gyrase binding site with a high fitness score and a minimum energy barrier of −7.651 kcal/mol. These findings indicate that P. indica exhibits significant antimicrobial activity, primarily due to the presence of plumbagin. The specificity of plumbagin toward DNA gyrase in S. aureus indicates the feasibility of utilizing P. indica for developing new drug leads against drug resistant microbial strain. Communicated by Ramaswamy H. Sarma